2014
DOI: 10.1364/josab.31.000806
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected unidirectional perfect absorption of light in a freestanding optical thin metallic grating with extremely small filling factor

Abstract: In this paper, we predict an unexpected enhanced optical absorption (OA) phenomenon in an optical thin (60 nm) freestanding metallic grating. After introducing periodical back grooves to the grating, the absorption could be enhanced up to 95% for light incident from the topside, which is inhibited lower than 10% for light incident from the bottom side. Physically it is ascribed to the strong modulation effect of the surface plasmons (SPs)/or charge distribution on the back surface of the grating by the grooves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This is intuitive as -in contrast to thin film interference, where the resonating wavelength depends on the angle of incidencethe present resonance is confined to the wires. 27,29 Fully exploring this effect would go beyond the scope of this article, but proper tuning of the parameters also led to very high absorbance values (above 95%) in our simulations. The angle of incidence on the other hand determines how strong the incident field can couple to this resonance (weaker coupling at increasing angles of incidence is especially visible for aluminum in the darker blue colors in Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…This is intuitive as -in contrast to thin film interference, where the resonating wavelength depends on the angle of incidencethe present resonance is confined to the wires. 27,29 Fully exploring this effect would go beyond the scope of this article, but proper tuning of the parameters also led to very high absorbance values (above 95%) in our simulations. The angle of incidence on the other hand determines how strong the incident field can couple to this resonance (weaker coupling at increasing angles of incidence is especially visible for aluminum in the darker blue colors in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Research on similar structures however showed that strongly enhanced absorption may result from the introduction of grooves. 27,29 Fully exploring this effect would go beyond the scope of this article, but proper tuning of the parameters also led to very high absorbance values (above 95%) in our simulations.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…First, each cross-grating is demonstrating equivalent sensitivity over a certain range of CDs summing to about one-third of the total range. Second, there is a general trend visible based on the fill factor -the ratio of area filled by the grating to the total area [25] -which is expected due to the nature of localized plasmons.…”
Section: Infinite Cross-gratingmentioning
confidence: 99%
“…For these optoelectronic devices, a high transmission of light through MF is necessary. A simple way to enhance the transmission is to carve channels (holes or slits) in the MF, for which the extraordinary optical transmission phenomena of lights were observed [1]- [5], which are widely explained as the excitation of surface plasmons resonance [1]- [4] or spoof surface plasmons for highly conducting metals [6] and/or the Fabry-Pérot (FP)-like cavity mode resonances in these optical channels [5], [7]. However, these transmissions are usually narrowband due to their resonant nature.…”
Section: Introductionmentioning
confidence: 99%